THOMAS MERTON: A PERSONAL ODYSSEY - Nyme, Katherine (Journal of Dharma, 1979)
More than ten years have passed since the death of Thomas Merton. Yet to many, he still seems very much alive. Merton was a multi-faceted individual. He was a monk, a priest, an author, a poet, a revolutionary, a peacemaker. Described as a saint by some; he is most often thought of as the Western model of a contemplative mystic. Merton's personal odyssey into mysticism will be explored in this essay.